Preparation and Characterization of Cellulose Nanocrystal Extraction From Pennisetum hydridum Fertilized by Municipal Sewage Sludge via Sulfuric Acid Hydrolysis - Xiaoshan Yu (Frontiers Media S.A., 2021)
This research focuses on the preparation of cellulose nanocrystals (CNCs) from Pennisetum hydridum fertilized by municipal sewage sludge (MSS) through sulfuric acid hydrolysis in different acid concentrations (40–65%), temperature (room temperature ∼55°C), and reaction time (50–120 min). The results showed that the obtained CNC possessed stable dispersion in water. The length of CNCs reached 272.5 nm under the condition of room temperature (RT), 65% acid concentration, and 120 min reaction time, and the diameter was within 10 nm. Furthermore, Fourier transform infrared (FTIR) showed that the CNC still kept the cellulose type I structure. The crystallinity of CNCs increased to the maximum by 18.34% compared with that of delignified Pennisetum hydridum fibers. Thermogravimetry (TG) illustrated the thermal stability of CNCs was lower than that of delignified Pennisetum hydridum fibers due to the introduction of sulfate groups in the cellulose. This study demonstrated that Pennisetum hydridum fertilized by MSS might be a suitable raw material for CNCs. This implies meaningful resource utilization of MSS and Pennisetum hydridum.